Karakteristik Ekstrak Kulit Buah Kakao (Theobroma cacao L.) sebagai Sumber Antioksidan pada Perlakuan Konsentrasi Pelarut dan Ukuran Partikel - Miranda, Praycelia Marissa; Ganda Putra, G.P.; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 1 (2020): MaretDO - 10.24843/JRMA.2020.v08.i01.p04, 2020)
Cocoa pod husk is the highest waste of the cocoa fruit processing and has not been used optimally.The waste pod husk of cocoa contain polyphenol that can be used for antioxidants. Polyphenol on pod husk of cocoa can be extract using extraction method. This study aims were to determine the effect of the solvent concentration and particle size o n the extract of pod husk of cocoa as a source of antioxidants and to determine the best of solvent concentration and particle size to produce extract of pod husk of cocoa as a source of antioxidant. The study was the experimental research which designed by using randomized block desin (RBD) with two factors . The first factor was solvent concentration that consists of 70, 80 and 90 percent of ethanol.The second factor wasparticle size that that consists of 40, 60 and 80 mesh. The data were analyzed by analysis of variance (ANOVA) and continued with the Tukey test. The results showed that the solvent concentration and particle size had very significant effect while the interaction did not affect significantly of the yield, total phenolics and antioxidant capacity of the extract of pod husk of cocoa. 90 percent of ethhanol concentration and 80 mesh of particle size was the best treatment for extracting pod husk of cocoa as a source of antioxidants with characteristic 10.78±0.61 percent of yields, 110.65±0.80 mg GAE/g of total phenolics and 55.08±0.78 mg GAEAC/g of antioxidant capacity . Keywords : pod husk cocoa, solvent concentration, particle size, antioxidants